Analisis Pengaruh Authenticity Terhadap Destination Loyalty Kota Penang Malaysia Yang Dimediasi Oleh Heritage Tourism - Anggraini, Ratih; Wang, Windy Graciela (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
Heritage tourism is an interesting destination for many people because it has its own culture and characteristics. Heritage tourism is able to attract more tourists because each cultural heritage tourism has a different culture. The city of Penang is one of the world heritage destinations that included in the UNESCO World Heritage List. As a cultural heritage destination, Penang City maintains the preservation of culture that has existed for a long time. Tourists who visit the city of Penang come from various countries, one of it is Indonesia. This research examines authenticity, heritage tourism, and destination loyalty in Penang City and analyzes how each variable influence, related, and has a positive and significant impact to each other. The research uses quantitative methods with sample collection carried out through the snowball sampling method. Data testing was carried out using the PLS-SEM test to test the hypothesis and influence between variables in this research. The research results show that authenticity has a positive and significant effect on destination loyalty which is mediated by heritage tourism. Therefore, the culture in Penang City needs to be maintained and preserved to maintain the authenticity of this destination. Keywords: Authenticity; Destination Loyalty; Heritage Tourism; Penang City